Model of Corporate Social Responsibility Based on Transparency in the Digital Ecosystem of Bank Resalat Using Meta-Synthesis - Kermani, Masood; Karimi , Mohammad Reza; Rahimi, Abdolrahim (Digital Transformation and Administration Innovation, 2026)
This study aims to design a Corporate Social Responsibility (CSR) model based on transparency within the digital ecosystem of Bank Resalat. The primary objective is to identify the key components and subcomponents necessary for a transparent CSR approach, emphasizing the digital platforms and social media's role in fostering trust. To achieve this, a meta-synthesis method is applied, analyzing scholarly articles published between 2000 and 2025, sourced from reputable academic databases such as ProQuest, Web of Science, Emerald, and Elsevier. Data collection involves systematic elimination sampling and content analysis of 34 selected studies. The PEISMA framework is utilized for coding and categorizing these components. The results highlight several critical components of transparency in CSR, including digital reporting, stakeholder interaction, protection of customer data, digital education, and the use of new technologies for transparency. These findings emphasize the importance of digital transparency in enhancing trust and brand loyalty, positioning Bank Resalat as a leader in digital banking. The study concludes that a structured CSR model based on transparency can guide banks in effectively engaging with their communities, thereby improving their brand perception and performance.